Preparation of Ni-Ti Shape Memory Alloy by Spark Plasma Sintering Method - Salvetr, Pavel; Kubatík, Tomáš František; Novák, Pavel (Manufacturing Technology Journal, 2016)
This paper aims to describe powder metallurgy methods of production Ni-Ti shape memory alloy - self-propagating high-temperature synthesis (SHS) and spark plasma sintering (SPS). There are compared microstructures and phase compositions of alloys produced by SHS and by a technology containing SHS, milling and SPS. At the same time there is determined the influence of the SPS sintering temperature on the structure of Ni-Ti alloy. Self-propagating high-temperature synthesis was initiated at 1100°C with process duration 20 minutes the heating rate of approx. 300 °C/min. The product is highly porous and contains undesirable Ti2Ni phase. The SPS technique allows to obtain product with low porosity. The disadvantages of SPS technique are growing amount of Ti2Ni phase and formation of other undesirable phases (Ni4Ti3 and Ni3Ti).
Keywords: powder metallurgy; reactive sintering; spark plasma sintering; Ni-Ti alloy